MORPHOLOGY, STRUCTURE AND MECHANICAL PROPERTIES OF NATURAL CELLULOSE FIBER FROM OIL PALM FROND FIBER (ELAEIS GUINEENSIS JACQ) - Sari, Martina Puspita; Purnowidodo, Anindito; Hamidi, Nurkholis (Jurnal Rekayasa Mesin, 2025)
Natural fiber is one of the innovations in the development of renewable materials from composites which are considered more environmentally friendly. One of the advantages is that it is biodegradable which are able to decompose in nature and does not leave residues that are harmful to the environment until now it has been developed in combination with various types of polymer matrices so that it can produce composites that have good strength. In this study, composites made from palm frond fiber (Elaeis guineensis Jacq) were characterized by a two-step treatment, namely alkalization using sodium hydroxide (NaOH) and the addition of a bleaching process using hydrogen peroxide (H2O2). single fiber and Weibull distribution methods, chemical properties testing including chemical composition of fiber content, FTIR, and physical property testing including diameter measurement and SEM observations. Thus, the optimal concentration of alkali and bleaching was produced in the two-step process between 5% NaOH concentration and H2O2 in terms of bonding characteristics, this was mainly due to the reduction of the amorphous part of the fiber. There was a color change after the OPFF was treated with NaOH and H2O2 where the color of the OPFF became brighter. The heat resistance value is inversely proportional to the thickness value after alkaline treatment. heat resistance increased while the diameter of the OPFF decreased with increasing concentration of NaOH and the addition of the second treatment H2O2. The best crystallinity index was obtained at 10% NaOH variation and the best cellulose content was obtained at 5% NaOH variation. Likewise, the tensile strength of TF without treatment experienced a significant increase (76%) with 5% NaOH - H2O2 treatment. The results of the FTIR (Fourier-transform Infrared Spectroscopy) test confirmed that the alkaline treatment and bleaching removed the hemicellulose content, impurities, and excessive water absorption. The surface of the treated OPFF becomes rougher. The etched surface shows interlocking with the matrix as shown in the SEM images. The effect of NaOH and H2O2 treatment on OPFF shows the potential of OPFF as a reinforcement for matrix polymer composites to reduce the use of synthetic fibers.